2000
DOI: 10.1007/bf03027957
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent for labour epidurals: what labouring women want to know

Abstract: Purpose: To determine A) what a labouring woman expects to hear about epidural analgesia before consenting, B) if she feels able to understand the risks and thereby assess if we are obtaining informed consent.Methods: Sixty actively labouring women were surveyed immediately after requesting an epidural. Demographic, labour, epidural and consent information were included in the questionnaire. Answers were categorical (yes/no, multiple choice) or scored on a scale from 0 to 10 (visual analogue scale).Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 5 publications
2
49
1
Order By: Relevance
“…16 Although there are several publications on the views, knowledge and concerns of health care providers regarding epidural analgesia for childbirth, there are few reports from women about the technique. 17,18 In sub-Saharan Africa, little information has been documented on the views of pregnant women about the use of epidural analgesia in labor. This may hinder widespread use of epidural analgesia should it be introduced by health institutions.…”
Section: Introductionmentioning
confidence: 99%
“…16 Although there are several publications on the views, knowledge and concerns of health care providers regarding epidural analgesia for childbirth, there are few reports from women about the technique. 17,18 In sub-Saharan Africa, little information has been documented on the views of pregnant women about the use of epidural analgesia in labor. This may hinder widespread use of epidural analgesia should it be introduced by health institutions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Their survey of 60 women in labour concluded that these women, who were able to conduct a 10 min interview while labouring, clearly were also able to consent to the proposed epidural.…”
mentioning
confidence: 99%
“…A study of patients in extreme pain, as measured by the Generalized Distress Index, found that there is no relationship between a patient's ability to make decisions and his or her distress index scores (Casarett et al 2003). Specific tests of the relationship between labor pain and ability to understand also found no relationship between physical incapacity and decision-making capacity (Jackson et al 2000). Although childbirth often involves pain and anxiety, there is no reason to think that women in labor should be presumed less competent to consent to interventions, including anesthesia and surgery, than other patients who suffer from stressful or painful conditions (Ladd 1989).…”
Section: Childbirth and Consentmentioning
confidence: 96%